New Trends in Cloud Computing - Štefániková, Victoria; Matuštík, Ondřej; Böhmová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The bachelor thesis deals with the latest trends in SaaS. The main aim of this thesis is to explore, evaluate and analyze new trends in Cloud Computing based on theoretical knowledge. The theoretical part of this thesis focuses on defining the very concept of Cloud Computing and brings the reader more detailed overview of terms related to this topic. This part of the bachelor thesis also deals with an issue around trends in Cloud Computing. The practical part focuses more closely on trends in the Cloud, specifically on trends in SaaS.This part is devided into three chapters, where the first chapter discusses the current state of Cloud Computing, the second chapter focuses on the most disruptive technologies that are predicted to change the cloud around SaaS in the future. The final chapter is an analysis of the most likely SaaS trends in the future. After reading the bachelor thesis, the reader will be familiar with the current situation of Cloud and will get an overview of the latest and predicted trends in SaaS.
Vedoucí práce: Ondřej Matuštík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses